TREATMENT OF FATE IN SHAKESPEAREAN AND CLASSICAL GREEK TRAGEDIES: A COMPARISON - Chowdhury, Takad Ahmed (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2020)
Fate is regarded as a central component in tragedy. The significant role of fate is recognized when, despite a character's heroic acts and good intentions, they face death simply because they are doomed to die. But studies confirm that fate does not play a similarly critical role in the tragic denouement of each play. This paper attempts a critical comparison on the role and nature of fate in the downfall of protagonists in the classical Greek and Shakespearean tragedies. By reviewing research-based articles and books, and by reading through selected texts in reader-response approach, this paper attempts to identify the entirely different natures of fate that came into play for the tragic heroes? downfall as portrayed in these two different ages. The findings manifest that the force behind the collapse of the heroes in the classical Greek tragedies was predominantly fate where the hero had little to do but to become a pawn in the hands of external forces beyond his control, while the force behind the tragic events is not external in the Shakespearean tragedies. Rather, the heroes themselves were, on the whole, responsible for their tragic downfalls due to their internal triggers.